The effect of the pronation position on COVID-19 patients with respiratory problems without intubation in the ICU: a literature review - Yuza Olsi Rahmi (Media Keperawatan Indonesia, 2022)
One of the causes of COVID-19 is a respiratory disorder characterized by mild, moderat to severe pneumonia. Symptomps can be seen by the decrease in oxygen saturation values in patients suffering from COVID-19, causing the patient’s, condition to be critical and must be treated in the ICU. This makes it very possible for patients to experience multi organ failure. The pronation position results in the homogenity of the lung alveoli, so that there is no hyperinflation in the ventral area of the lung and collapse of the dorsal lung, by using the pronation position, the recruitment of oxygentaion by the lungs in the dorsal area increase so that oxygen saturation in the body can increase. The purpose of this study was to analyze the effect of pronasition positioning on increasing oxygentaion in COVID-19 patients with mild to moderate respiratory distress in patients treated in the non-intubated ICU. The results from the four journals that have been reviewed show that giving a pronation position to COVID-19 patients with mild to moderate ARDS is able to increase oxygen saturation and can pevent patients from being intubated. Conclusion : the use of the prone position in mild to moderate respiratory disorders experience by COVID-19 patients is quite safe to be applied in the ICU treatment room.